PENGARUH KINERJA ENVIRONMENTAL, SOCIAL, GOVERNANCE (ESG) TERHADAP KINERJA PERUSAHAAN DENGAN KENDALA KEUANGAN SEBAGAI VARIABEL MODERASI (Studi pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia tahun 2016-2020) - Lola Rizky Bunga Pertiwi; Hersugondo Hersugondo (Diponegoro Journal of Management, 2023)
ABSTRACT The purpose of this study was to know and analyze the effect of environmental, social, governance performance or ESG performance on firm performance with financial constraints as moderating variable (studies of manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020). Firm performance is proxied by Return on Assets and Return on Sales, financial constraints proxied by Altman’s Z-score. This study uses secondary data obtained from the Bloomberg Database and the Company's Annual Report published in the Indonesia Stock Exchange (IDX). The population in this study is a manufacturing companies listed on the Indonesian Stock Exchange in 2016-2020. The sampling technique used is purposive sampling, so that the samples obtained were 23 companies. This study uses qualitative methods, using panel data regression analysis techniques and Random Effect Model (REM) with Eviews 9 program. The result of this study indicates that ESG performance has a positive and insignificant effect on firm performance. Financial constraints are able to moderate the effect of ESG performance on firm performance in positive and significant. Then it can be conclude that the higher value of ESG performance is not able to improve firm performance. And financial constraints can increase the effect of ESG performance on firm performance.